Synthesis of noble metal-based nanocomposites for enhanced catalytic performance - Liu, Ye (2017)
Noble metals have been applied as heterogeneous catalysts for a long time. In recent decades, it was found that noble metal nanostructures exhibit superior catalytic performance than their bulk counterpart owing to the high surface-to-volume ratio. However, it is challenging for single-component nanomaterials to achieve multiple goals such as catalytic activity, selectivity and stability. Noble metal nanocomposites thus have drawn growing attention spontaneously. This study aims to fabricate noble metal-based nanocomposites possessing enhanced catalytic performance. Experimental methods used include wet chemical reduction, solvothermal synthesis, and post synthetic modification. The as-synthesized materials were characterized by scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray diffraction (XRD) and many other techniques. Ultraviolet-visible Spectroscopy (UV-Vis) and gas chromatography (GC) were used to monitor the catalytic reactions. First of all, a facile and robust method was provided to prepare ultrathin bimetallic core-shell nanosheets (NSs), where the ultrathin 2D metallic NSs are incompletely covered by another atomically layered metal. Submonolayered Ru decorated-ultrathin Pd NSs was synthesized using this seed-mediated growth method for the first time, which is referred to as Pd@Ru NSs. The underpotential deposition process is responsible for the formation of Pd@Ru NSs. Impressively, the as-synthesized noble bimetallic Pd@Ru NSs exhibit superior catalytic performance toward the reduction of 4-nitrophenol and the semihydrogenation of 1-octyne as compared to the pure ultrathin Pd NSs and Ru NSs. The second work elaborated the synthesis of 2D noble metal/porphyrinic metal-organic framework (MOF) composite via a seed-mediated growth method. Owing to the synergistic effect between the photothermal effect of Pd and the light-harvesting ability of the porphyrinic MOF Cu-TCPP, the composite exhibits superior catalytic performance than pure Pd NSs in the photo-oxidation of benzyl alcohol under high light irradiation intensity. Furthermore, the catalytic activity of the composite can be altered upon different light irradiation intensities. In the last work, it was demonstrated that the pore size of NPs/MOF composite can be modified with alkyl chains of different lengths. The obtained products showed enhanced size-selective catalytic performance in the hydrogenation of olefins (triphenylethylene, trans-stilbene, cyclooctene), which revealed the flexibility of MOFs as supporting materials for heterogeneous catalysis. Based on these accomplished works, a conclusion can be drawn that noble metal based nanocomposites provide better options for some chemical reactions in the following aspects. Firstly, coupling noble metal with another component may induce a synergistic effect, which can promote the catalytic activity. Secondly, combing noble metal with some functional materials, such as MOFs, can introduce some additional properties, which may be beneficial to the catalytic activity as well as selectivity. Last but not least, supporting materials can promote the dispersion and stability of noble metal nanostructures.